BIMBINGAN BAGI ANAK TUNA CAKAP BELAJAR DI SD GMIT 23 RUILAK - Feni Diana Djaha; Trivonia Ata, Serlyn Letding , Yessy Mata, Petrus Mau Tellu Dony, Halena Muna Bekata (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to discuss guidance for students of GMIT 23 Ruilak Elementary School. The main problem is that students experience difficulties in reading, writing, and arithmetic and face challenges in social-emotional development. GMIT 23 Ruilak Elementary School students need special education services tailored to the form and level of difficulties they experience. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The data sources used are primary and secondary data sources. The results of the study indicate that GMIT 23 Ruilak Elementary School students experience difficulties in reading, writing, and arithmetic and face challenges in social-emotional development. The causative factors include internal factors such as mild brain disorders and emotional and external factors such as heredity, negative experiences, less supportive environments, family pressure, and lack of parental attention and guidance. Although teachers have also conducted initial assessments, academic guidance, and emotional support, these efforts have not been optimal due to limited special programs and professional staff. Therefore, collaboration between schools, teachers, parents, and related parties is needed to create inclusive and adaptive learning for GMIT 23 Ruilak Elementary School students.